St. Thomas with Archangels Michael and Gabriel - Ghosh, Ayan (2023)
The southwest corner of St. Thomas Church has triple stained glass windows showing the figures of St. Thomas (in the center) flanked by the Archangels St. Michael (right) and St. Gabriel (left). Their respective names appear at the bottom of each panel.